Efficiency Measurement and Determinant Factors of Marine Economy in China: Based on the Belt and Road Perspective. (23rd April 2021) - Wang, Yinyin; Xue, Conghua; Li, Huimin; Yu, Kaizhi
Abstract : Analyzing the evolution characteristics and influencing factors of marine economic efficiency is the foundation to improve the quality of marine economic development. A super-efficiency Slacks-Based Measure (SBM) model is applied to measure the marine economic efficiency of 11 coastal provinces between 2006 and 2017 in China. Time series and standard deviation ellipse methods are used to analyze its temporal and spatial characteristics. The influencing factors of efficiency are analyzed using the Bayesian model averaging (BMA) method based on the indicator system constructed on the relationship between the Belt and Road and marine economic efficiency. The research found that (1) the average change of marine economic efficiency is not large, and the efficiency values among most provinces are relatively stable. (2) The center of gravity of marine economic efficiency gradually shifts from the northeast to the southwest; the spatial scope continues to shrink, the level of flatness indicates increase at first followed by decrease, and the direction angle shows a fluctuating trend. (3) The compliance rate of industrial wastewater discharge and the diversification of the marine industry structure have strong explanatory capacity in marine economic efficiency in the coastal areas. This research proposed the specific path to improve the efficiency of marine economy and facilitate quality development under the "Belt and Road" initiative from the aspects of the optimization of the marine industry structure, the integrated construction of transportation, the development of opening to the outside world, the progress of marine science and technology, and the improvement of the marine ecological environment.